AN X-RAY ABSORPTION SPECTROSCOPY STUDY OF THE STRUCTURE AND REVERSIBILITY OF COPPER ADSORBED TO MONTMORILLONITE CLAY - Morton J.D.; Semrau J.D.; Hayes K.F. (My University, 2001)
X-ray absorption spectroscopy (XAS) and adsorption-desorption measurements have been performed to assess the relationship between the structure and reversibility of copper complexes on montmorillonite clay. By varying the solution pH and background electrolyte concentration, the adsorption of copper on either the edge sites or permanent charge sites of montmorillonite was controlled. This allowed the structure and reversibility of copper complexes on each of these site types to be assessed independently of each other. XAS analysis of copper adsorbed on the permanent charge sites indicated outer-sphere surface complexes, with these complexes showing sorption reversibility. For copper complexes formed on the edge sites of montmorillonite, XAS data confirmed the presence of monomer and dimer copper surface complexes. Sorption irreversibility at edge sites was noted at copper coverages less than 20 μmoles/g clay at pH=4.2 and at coverages greater than 50 μmoles/g clay at pH=6.8. At pH=6.8, higher Cu-Cu coordination numbers indicated the copper sorption irreversibility may be due, in part, to the formation of dimer surface complexes. The coordination numbers at pH=4.2 indicated the irreversibility could be due to the formation of dimers or due to formation of surface complexes on high energy edge sites.